High-temperature-resistant monomer casting nylon material and preparation method thereof
By adding dodecanollam, basalt fibers, high-temperature resistant fibers and graphite particles to the monomer cast nylon material, the problem of reducing tensile strength and self-lubricity of monomer cast nylon material at high temperature in the prior art is solved, and the problem of reducing tensile strength and self-lubricity of monomer cast nylon material at high temperature is achieved. Higher mechanical properties and service life.
Patent Information
- Application Number
- CN202510000729.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-02-07
AI Technical Summary
The tensile strength and self-lubricity of existing monomer cast nylon materials will be reduced at high temperatures, resulting in reduced effectiveness of bearings and bearing sleeves and reduced service life.
The nylon material is cast with high temperature resistant monomer composed of dodecanollam, basalt fibers, high temperature resistant fibers and graphite particles. Through specific component ratios and preparation methods, the modulus of the material is enhanced and the friction coefficient is reduced.
It improves the mechanical properties of monomer cast nylon material, increases its tensile strength and self-lubricity at high temperatures, extends service life, and improves the density and wear resistance of the material.
Smart Images

Figure CN119391176A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of organic polymer compounds, in particular to a compound obtained by a reaction other than carbon-carbon unsaturated bonds, and in particular to a high-temperature resistant monomer casting nylon material and a preparation method thereof. Background Art
[0002] Monomer cast nylon, also known as MC nylon, is an engineering plastic with excellent physical and mechanical properties. Monomer cast nylon is a material that is formed by directly polymerizing caprolactam or other lactam monomers in a mold and solidifying them through base-catalyzed polymerization.
[0003] Monomer cast nylon has high mechanical strength, self-lubrication, rigidity and wear resistance, and can support high loads and resist wear, which makes it an ideal material for manufacturing bearings and bearing sleeves. In mechanical engineering, especially those occasions that require high loads and high-speed operation, such as the transmission systems of equipment such as cranes and elevators, the performance requirements for bearings and bearing sleeves are extremely high. Monomer cast nylon can meet these requirements and ensure the stable operation of the equipment.
[0004] However, during the use of bearings and bearing sleeves, due to the need for continuous friction, the bearings and bearing sleeves will generate a lot of heat. Although the monomer cast nylon itself has a certain heat resistance, the tensile strength and self-lubricating properties of the monomer cast nylon will be reduced at high temperatures, which will reduce the use effect of the bearings and bearing sleeves and shorten their service life.
[0005] Therefore, it is necessary to improve the monomer cast nylon material in the prior art to solve the above problems. Summary of the invention
[0006] The present invention overcomes the deficiencies of the prior art and provides a high temperature resistant monomer cast nylon material and a preparation method thereof, aiming to solve the defect in the prior art that the tensile strength and self-lubricating property of the monomer cast nylon material are reduced due to high temperature during use.
[0007] To achieve the above object, the technical solution adopted by the present invention is: a high temperature resistant monomer cast nylon material, composed of component A, component B and component C, wherein: The A component is laurolactam; The B component includes: basalt fiber, high temperature resistant fiber and graphite particles, and the mass ratio of the basalt fiber, the high temperature resistant fiber and the graphite particles is: 100-120:50-60:30-40; The C component includes: a catalyst, a co-catalyst and a surface modifier, and the mass ratio of the catalyst, the co-catalyst and the surface modifier is: 1-10:10-14:10-25; The mass ratio of the A component, the B component and the C component is 84:100:10-14:3-5.
[0008] In a preferred embodiment of the present invention, the basalt fiber is prepared based on basalt ore, and the raw materials for preparing the basalt fiber include basalt ore, quartz sand, quicklime, a wetting agent and a coupling agent, wherein the mass proportion of the basalt ore is greater than 65%.
[0009] In a preferred embodiment of the present invention, the high temperature resistant fiber is aromatic sulfone fiber, and the fineness of the high temperature resistant fiber is 5D-7D.
[0010] In a preferred embodiment of the present invention, the graphite particles include large graphite particles and small graphite particles, the particle diameters of the large graphite particles and the small graphite particles are 60-100 μm and 20-40 μm, respectively, and the mass ratio between the large graphite particles and the small graphite particles is 1:4-6.
[0011] In a preferred embodiment of the present invention, the fineness of the basalt fiber is 6D-10D, and the length of the basalt fiber is consistent with the length of the high temperature resistant fiber.
[0012] In a preferred embodiment of the present invention, the catalyst, the co-catalyst and the surface modifier are vinyl alcohol, acetyl caprolactam and distearoyloxyisopropylaluminate, respectively.
[0013] To achieve the above object, the second technical solution adopted by the present invention is: a method for preparing a high temperature resistant monomer cast nylon material, comprising the following steps: S1: heating the laurolactam monomer to a molten state in a closed environment, the heating condition is a constant temperature oil bath of 270-300° C., the heating time after the molten state is 30-60 minutes, and vacuuming is performed in the molten state to obtain molten laurolactam; S2: adding a catalyst to the molten laurolactam, and continuing to heat at 270-280° C. for 20-30 min after stirring to obtain polymerized laurolactam; S3: adding quaternary ammonium salt powder to the polymerized laurolactam, wherein the mass ratio of the polymerized laurolactam to the quaternary ammonium salt powder is 20-30:1, and stirring at a temperature of 240-260° C. for 1-2 hours to obtain a modified nylon material; S4: adding basalt fiber, high temperature resistant fiber and graphite particles to the modified nylon material in sequence, and heating to 285-300° C. for 2-4 hours to obtain a high temperature resistant nylon material; S5: Casting the high temperature resistant nylon material into a mold preheated to 160-180° C., and always maintaining the mold temperature for 20-30 minutes and then cooling naturally, performing centrifugal treatment during the cooling process, to obtain a high temperature resistant monomer cast nylon material.
[0014] In a preferred embodiment of the present invention, the graphite particles are modified by aluminum sol, and the modification process is to immerse the graphite particles in nano aluminum sol for 1.5-2h, the solid particle size diameter in the nano aluminum sol is 10-30nm, and the concentration of the nano aluminum sol is 15-25%.
[0015] In a preferred embodiment of the present invention, the diameter of the laurolactam monomer is 10-14 μm, and the length of the basalt fiber is 15-18 mm.
[0016] To achieve the above-mentioned purpose, the third technical solution adopted by the present invention is: an application of a high-temperature resistant monomer cast nylon material, wherein the application of the high-temperature resistant monomer cast nylon material is a bearing and a bearing sleeve.
[0017] The present invention solves the defects existing in the background technology and has the following beneficial effects: (1) The present invention provides a high temperature resistant monomer cast nylon material, comprising laurolactam, basalt fiber, high temperature resistant fiber and graphite particles. The basalt fiber, high temperature resistant fiber and graphite particles can respectively enhance the modulus of the monomer cast nylon and reduce the friction coefficient of the monomer cast nylon material on the basis of the high temperature resistance of laurolactam. Compared with the monomer cast nylon material in the prior art, the mechanical properties of the monomer cast nylon material can be enhanced, the tensile strength and self-lubricating property of the monomer cast nylon material can be increased, and the defects of the monomer cast nylon material in the prior art that the tensile strength and self-lubricating property are reduced under high temperature conditions can be solved.
[0018] (2) In the present invention, the graphite particles include large graphite particles and small graphite particles. The mixed use of large graphite particles and small graphite particles can more effectively fill the nylon matrix. Compared with the prior art, it can reduce the pores inside the nylon matrix, improve the density of the material, and improve the mechanical strength of the monomer cast nylon material.
[0019] (3) In the present invention, basalt fiber and arylsulfone fiber are added during the preparation process of monomer cast nylon, which can form a grid structure in the nylon matrix. Compared with the prior art, the grid structure can form a stable structure. The high temperature resistance of basalt fiber and arylsulfone fiber can improve the heat resistance of the grid structure, increase the stability of the monomer cast nylon material at high temperature, and maintain the tensile strength and self-lubricating property of the monomer cast nylon.
[0020] (4) In the present invention, the graphite particles are modified by aluminum sol, and the modification process is to immerse the graphite particles in nano aluminum sol. The aluminum sol modification can further improve the self-lubricating property of the graphite. Compared with the prior art, the wear resistance and self-lubricating property of the monomer cast nylon material at high temperature are improved. Moreover, the colloidal particles are negatively charged, which can promote the combination of graphite and the positively charged nylon matrix, thereby improving the mechanical properties of the monomer cast nylon material. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art are briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative work. Figure 1 It is a method step diagram of a preferred embodiment of the present invention. DETAILED DESCRIPTION
[0022] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein. Therefore, the protection scope of the present invention is not limited to the specific embodiments disclosed below.
[0024] A high temperature resistant monomer cast nylon material, consisting of component A, component B and component C, wherein: Component A is laurolactam; Component B includes: basalt fiber, high temperature resistant fiber and graphite particles, and the mass ratio of basalt fiber, high temperature resistant fiber and graphite particles is: 100-120:50-60:30-40; Component C includes: a catalyst, a co-catalyst and a surface modifier, and the mass ratio of the catalyst, the co-catalyst and the surface modifier is: 1-10:10-14:10-25; The mass ratio between component A, component B and component C is 84:100:10-14:3-5.
[0025] Basalt fiber is made from basalt ore. The raw materials for basalt fiber include basalt ore, quartz sand, quicklime, wetting agent and coupling agent. The mass of basalt ore accounts for more than 65%. The wetting agent is polyvinyl alcohol and the coupling agent is γ-aminopropyltriethoxysilane. The addition of basalt fiber can significantly improve the mechanical strength and modulus of nylon materials, thereby enhancing the physical properties of the final product.
[0026] The high temperature resistant fiber is aromatic sulfone fiber, and the fineness of the high temperature resistant fiber is 5D-7D. Aromatic sulfone fiber itself has a very high melting point. Fibers with moderate fineness can be mixed with other materials without sacrificing heat resistance to improve the heat resistance of the overall composite material. The fineness range of 5D-7D means that the fiber is finer, which helps to better disperse during mixing and casting, thereby improving processing performance. Both basalt fiber and aromatic sulfone fiber have excellent high temperature resistance. Their combination can form a high temperature resistant network structure in the nylon matrix, significantly improving the overall heat resistance of the material. In a high temperature environment, the presence of the two fibers helps to maintain the structural stability of the material and reduce performance degradation caused by increased temperature.
[0027] The graphite particles include large graphite particles and small graphite particles. The particle diameters of the large graphite particles and the small graphite particles are 60-100μm and 20-40μm, respectively, and the mass ratio between the large graphite particles and the small graphite particles is 1:4-6. Graphite particles have good thermal conductivity. Particles of different sizes can improve the thermal conductivity efficiency of the material and help dissipate heat. The mixed use of large graphite particles and small graphite particles can more effectively fill the nylon matrix, reduce pores, and improve the density of the material.
[0028] The fineness of basalt fiber is 6D-10D, and the length of basalt fiber is consistent with that of high temperature resistant fiber. Basalt fiber with moderate fineness is easier to disperse evenly in the nylon matrix and avoid aggregation, thereby improving the uniformity and overall performance of the composite material. The length of basalt fiber and high temperature resistant fiber is consistent, which helps to maintain the stability of the material in a high temperature environment and reduce damage caused by thermal stress.
[0029] The catalyst, co-catalyst and surface modifier are vinyl alcohol, acetyl caprolactam and distearyloxyisopropylaluminate. Vinyl alcohol as a catalyst can accelerate the polymerization reaction of nylon monomer, increase the reaction rate and shorten the production cycle. Acetyl caprolactam as a co-catalyst can synergize with the main catalyst to further improve the efficiency and yield of the polymerization reaction. Distearyloxyisopropylaluminate as a surface modifier can improve the surface properties of nylon materials, improve surface smoothness, reduce friction coefficient and enhance wear resistance.
[0030] like Figure 1As shown, in order to achieve the above purpose, the second set of technical solutions adopted by the present invention is: a method for preparing a high temperature resistant monomer cast nylon material, comprising the following steps: S1: The laurolactam monomer is heated to a molten state in a closed environment, the heating condition is a constant temperature oil bath of 270-300°C, the heating time after the molten state is 30-60min, and a vacuum treatment is performed in the molten state to obtain molten laurolactam; the constant temperature oil bath ensures that the laurolactam monomer is uniformly melted to avoid local overheating, and the vacuum treatment removes bubbles and impurities in the molten laurolactam to improve the purity and performance of the material.
[0031] S2: adding a catalyst to the molten laurolactam, and continuing to heat at 270-280° C. for 20-30 min after stirring to obtain polymerized laurolactam.
[0032] S3: Add quaternary ammonium salt powder to polymerized laurolactam, the mass ratio between polymerized laurolactam and quaternary ammonium salt powder is 20-30:1, and stir at a temperature of 240-260°C for 1-2h to obtain a modified nylon material; the quaternary ammonium salt can combine with polymerized laurolactam, and dibutyltin dilaurate is added for catalysis, and the mass ratio between the added dibutyltin dilaurate and polymerized laurolactam is 1:100-200. The quaternary ammonium salt used is N-dimethyl-N-(acryloyloxyethyl)-N-(2-hydroxyethyl) ammonium chloride, and the quaternary ammonium salt used can combine with polymerized laurolactam and give polymerized laurolactam a positive charge, thereby adjusting the charge distribution in polymerized laurolactam.
[0033] S4: Add basalt fiber, high temperature resistant fiber and graphite particles to the modified nylon material in sequence, and heat to 285-300℃ for 2-4h to obtain high temperature resistant nylon material; basalt fiber and high temperature resistant fiber (such as aromatic sulfone fiber) have excellent heat resistance, and their addition can significantly improve the heat resistance of nylon material. High temperature mixing helps the fiber and filler to be evenly dispersed in the nylon matrix to avoid aggregation, thereby improving the processing performance of the material. The addition of graphite particles can improve the self-lubrication of the material, reduce friction and wear, and extend the service life. The addition of graphite particles can improve the processing performance of the material, reduce viscosity during processing, and facilitate molding and processing.
[0034] S5: Casting the high temperature resistant nylon material into a mold preheated to 160-180° C. and always maintaining the mold temperature for 20-30 minutes and then cooling naturally. Centrifugation is performed during the cooling process to obtain the high temperature resistant monomer cast nylon material.
[0035] The graphite particles are modified by aluminum sol. The modification process is to immerse the graphite particles in nano aluminum sol for 1.5-2h. The solid particle size in the nano aluminum sol is 10-30nm in diameter and the concentration of the nano aluminum sol is 15-25%. The aluminum particles in the aluminum sol can form chemical bonds with the surface of the graphite particles, enhancing the interfacial bonding between the graphite particles and the nylon matrix. The colloidal particles are sticky and can be tightly combined with the graphite particles. The nanoparticles in the aluminum sol can improve the dispersion of the graphite particles in the nylon matrix, avoid agglomeration, and thus improve the uniformity of the composite material. Aluminum has a high melting point and good thermal stability. The graphite particles modified by aluminum sol can improve the stability of the composite material in a high temperature environment.
[0036] The diameter of the laurolactam monomer is 10-14μm, and the length of the basalt fiber is 15-18mm. This size range helps the monomer melt evenly during the heating process, avoiding uneven melting caused by oversized or undersized particles. Basalt fibers of appropriate length can better combine with the nylon matrix and improve the tensile strength and modulus of the composite material. Longer basalt fibers can improve the wear resistance of the composite material and extend the service life of the material.
[0037] To achieve the above purpose, the third technical solution adopted by the present invention is: an application of a high temperature resistant monomer cast nylon material, and the application of the high temperature resistant monomer cast nylon material is a bearing and a bearing sleeve. The high temperature resistant monomer cast nylon material can maintain stable performance in a high temperature environment and is suitable for bearings and bearing sleeves that need to operate under high temperature conditions.
[0038] Embodiment 1
[0039] This embodiment provides a high temperature resistant monomer cast nylon material, and the preparation process is as follows: S1: heating the laurolactam monomer with a monomer diameter of 12 μm to a molten state in a closed environment, the heating condition is a constant temperature oil bath of 270° C., the heating time after the molten state is 60 minutes, and vacuum treatment is performed in the molten state to obtain molten laurolactam.
[0040] S2: vinyl alcohol, acetyl caprolactam and distearoyloxyisopropyl aluminate are added to molten laurolactam in sequence, the mass ratio of vinyl alcohol, acetyl caprolactam and distearoyloxyisopropyl aluminate is 1:2:3, the mass ratio of the total mass of vinyl alcohol, acetyl caprolactam and distearoyloxyisopropyl aluminate to the molten laurolactam is 40:1, and after stirring, heating is continued at 280°C for 20 minutes; polymerized laurolactam is obtained.
[0041] S3: Add N-dimethyl-N-(acryloyloxyethyl)-N-(2-hydroxyethyl) ammonium chloride and dibutyltin dilaurate to polymerized laurolactam, the mass ratio of polymerized laurolactam, N-dimethyl-N-(acryloyloxyethyl)-N-(2-hydroxyethyl) ammonium chloride and dibutyltin dilaurate is 100:4:1, and stir at 250°C for 1h to obtain a modified nylon material.
[0042] S4: basalt fiber, sulfone fiber, graphite particles and distearoyloxyisopropylaluminate are added to the modified nylon material in sequence, the mass ratio of the added distearoyloxyisopropylaluminate to the distearoyloxyisopropylaluminate in the modified nylon material is 2:3, the mass ratio of basalt fiber, sulfone fiber and graphite particles is 6:3; 2, the mass ratio of the total mass of basalt fiber, sulfone fiber and graphite particles to the modified nylon material is 1:12, the fineness of basalt fiber and sulfone fiber is 8D and 6D respectively, the basalt fiber is 1:12, the fineness of basalt fiber and sulfone fiber is 8D and 6D respectively, the mass ratio of basalt fiber to basalt fiber is 1:12, the mass ratio of basalt fiber to sulfone ... The length of the fiber and the aryl sulfone fiber is 15 mm, the graphite particles are divided into large graphite particles and small graphite particles, the particle diameters of the large graphite particles and the small graphite particles are 80 μm and 30 μm respectively, the mass ratio between the large graphite particles and the small graphite particles is 1:4, the graphite particles are modified by aluminum sol, and the modification process is to immerse the graphite particles in nano-aluminum sol for 2 hours, the solid particle size diameter in the nano-aluminum sol is 20 nm, the concentration of the nano-aluminum sol is 15%, and it is heated to 285°C for 2 hours to obtain a high temperature resistant nylon material.
[0043] S5: Casting the high temperature resistant nylon material into a mold preheated to 180° C. and always maintaining the mold temperature for 30 minutes and then cooling naturally. Centrifugal treatment is performed during the cooling process to obtain the high temperature resistant monomer cast nylon material.
[0044] Embodiment 2
[0045] This embodiment provides a high temperature resistant monomer cast nylon material, and the preparation process is as follows: S1: heating the laurolactam monomer with a monomer diameter of 12 μm to a molten state in a closed environment, the heating condition is a constant temperature oil bath of 270° C., the heating time after the molten state is 60 minutes, and vacuum treatment is performed in the molten state to obtain molten laurolactam.
[0046] S2: vinyl alcohol, acetyl caprolactam and distearoyloxyisopropyl aluminate are added to molten laurolactam in sequence, the mass ratio of vinyl alcohol, acetyl caprolactam and distearoyloxyisopropyl aluminate is 1:2:3, the mass ratio of the total mass of vinyl alcohol, acetyl caprolactam and distearoyloxyisopropyl aluminate to the molten laurolactam is 40:1, and after stirring, heating is continued at 280°C for 20 minutes; polymerized laurolactam is obtained.
[0047] S3: Add N-dimethyl-N-(acryloyloxyethyl)-N-(2-hydroxyethyl) ammonium chloride and dibutyltin dilaurate to polymerized laurolactam, the mass ratio of polymerized laurolactam, N-dimethyl-N-(acryloyloxyethyl)-N-(2-hydroxyethyl) ammonium chloride and dibutyltin dilaurate is 100:4:1, and stir at 250°C for 1h to obtain a modified nylon material.
[0048] S4: basalt fiber, sulfone fiber, graphite particles and distearoyloxyisopropylaluminate are added to the modified nylon material in sequence, the mass ratio of the added distearoyloxyisopropylaluminate to the distearoyloxyisopropylaluminate in the modified nylon material is 2:3, the mass ratio of basalt fiber, sulfone fiber and graphite particles is 6:3; 2, the mass ratio of the total mass of basalt fiber, sulfone fiber and graphite particles to the modified nylon material is 1:10, the fineness of basalt fiber and sulfone fiber is 8D and 6D respectively, the basalt fiber is 1:10, the fineness of basalt fiber and sulfone fiber is 8D and 6D respectively, the mass ratio of basalt fiber to basalt fiber is 1:10, the mass ratio of basalt fiber to sulfone ... The length of the fiber and the aryl sulfone fiber is 15 mm, the graphite particles are divided into large graphite particles and small graphite particles, the particle diameters of the large graphite particles and the small graphite particles are 80 μm and 30 μm respectively, the mass ratio between the large graphite particles and the small graphite particles is 1:4, the graphite particles are modified by aluminum sol, and the modification process is to immerse the graphite particles in nano-aluminum sol for 2 hours, the solid particle size diameter in the nano-aluminum sol is 20 nm, the concentration of the nano-aluminum sol is 15%, and it is heated to 285°C for 2 hours to obtain a high temperature resistant nylon material.
[0049] S5: Casting the high temperature resistant nylon material into a mold preheated to 180° C. and always maintaining the mold temperature for 30 minutes and then cooling naturally. Centrifugal treatment is performed during the cooling process to obtain the high temperature resistant monomer cast nylon material.
[0050] Embodiment 3
[0051] This embodiment provides a high temperature resistant monomer cast nylon material, and the preparation process is as follows: S1: heating the laurolactam monomer with a monomer diameter of 12 μm to a molten state in a closed environment, the heating condition is a constant temperature oil bath of 270° C., the heating time after the molten state is 60 minutes, and vacuum treatment is performed in the molten state to obtain molten laurolactam.
[0052] S2: vinyl alcohol, acetyl caprolactam and distearoyloxyisopropyl aluminate are added to molten laurolactam in sequence, the mass ratio of vinyl alcohol, acetyl caprolactam and distearoyloxyisopropyl aluminate is 1:2:3, the mass ratio of the total mass of vinyl alcohol, acetyl caprolactam and distearoyloxyisopropyl aluminate to the molten laurolactam is 40:1, and after stirring, heating is continued at 280°C for 20 minutes; polymerized laurolactam is obtained.
[0053] S3: Add N-dimethyl-N-(acryloyloxyethyl)-N-(2-hydroxyethyl) ammonium chloride and dibutyltin dilaurate to polymerized laurolactam, the mass ratio of polymerized laurolactam, N-dimethyl-N-(acryloyloxyethyl)-N-(2-hydroxyethyl) ammonium chloride and dibutyltin dilaurate is 100:4:1, and stir at 250°C for 1h to obtain a modified nylon material.
[0054] S4: basalt fiber, sulfone fiber, graphite particles and distearoyloxyisopropylaluminate are added to the modified nylon material in sequence, the mass ratio of the added distearoyloxyisopropylaluminate to the distearoyloxyisopropylaluminate in the modified nylon material is 2:3, the mass ratio of basalt fiber, sulfone fiber and graphite particles is 6:3; 2, the mass ratio of the total mass of basalt fiber, sulfone fiber and graphite particles to the modified nylon material is 1:8, the fineness of basalt fiber and sulfone fiber is 8D and 6D respectively, the basalt fiber is 1:8, the fineness of basalt fiber and sulfone fiber is 8D and 6D respectively, the mass ratio of basalt fiber to graphite particles is 1:8, the mass ratio of basalt fiber to sulfone fiber ... The length of the fiber and the aryl sulfone fiber is 15 mm, the graphite particles are divided into large graphite particles and small graphite particles, the particle diameters of the large graphite particles and the small graphite particles are 80 μm and 30 μm respectively, the mass ratio between the large graphite particles and the small graphite particles is 1:4, the graphite particles are modified by aluminum sol, and the modification process is to immerse the graphite particles in nano-aluminum sol for 2 hours, the solid particle size diameter in the nano-aluminum sol is 20 nm, the concentration of the nano-aluminum sol is 15%, and it is heated to 285°C for 2 hours to obtain a high temperature resistant nylon material.
[0055] S5: Casting the high temperature resistant nylon material into a mold preheated to 180° C. and always maintaining the mold temperature for 30 minutes and then cooling naturally. Centrifugal treatment is performed during the cooling process to obtain the high temperature resistant monomer cast nylon material.
[0056] Embodiment 4
[0057] This embodiment provides a high temperature resistant monomer cast nylon material, and the preparation process is as follows: S1: heating the laurolactam monomer with a monomer diameter of 12 μm to a molten state in a closed environment, the heating condition is a constant temperature oil bath of 270° C., the heating time after the molten state is 60 minutes, and vacuum treatment is performed in the molten state to obtain molten laurolactam.
[0058] S2: vinyl alcohol, acetyl caprolactam and distearoyloxyisopropyl aluminate are added to molten laurolactam in sequence, the mass ratio of vinyl alcohol, acetyl caprolactam and distearoyloxyisopropyl aluminate is 1:2:3, the mass ratio of the total mass of vinyl alcohol, acetyl caprolactam and distearoyloxyisopropyl aluminate to the molten laurolactam is 40:1, and after stirring, heating is continued at 280°C for 20 minutes; polymerized laurolactam is obtained.
[0059] S3: Add N-dimethyl-N-(acryloyloxyethyl)-N-(2-hydroxyethyl) ammonium chloride and dibutyltin dilaurate to polymerized laurolactam, the mass ratio of polymerized laurolactam, N-dimethyl-N-(acryloyloxyethyl)-N-(2-hydroxyethyl) ammonium chloride and dibutyltin dilaurate is 100:4:1, and stir at 250°C for 1h to obtain a modified nylon material.
[0060] S4: basalt fiber, sulfone fiber, graphite particles and distearoyloxyisopropylaluminate are added to the modified nylon material in sequence, the mass ratio of the added distearoyloxyisopropylaluminate to the distearoyloxyisopropylaluminate in the modified nylon material is 2:3, the mass ratio of basalt fiber, sulfone fiber and graphite particles is 6:3; 2, the mass ratio of the total mass of basalt fiber, sulfone fiber and graphite particles to the modified nylon material is 1:6, the fineness of basalt fiber and sulfone fiber is 8D and 6D respectively, the basalt fiber is 1:6, the fineness of basalt fiber and sulfone fiber is 8D and 6D respectively, the mass ratio of basalt fiber to sulfone fiber is 8D and 6D respectively, the mass ratio of basalt fiber to sulfone fiber is 6:3, the mass ratio of basalt fiber to sulfone fiber and graphite particles is 6:3; The length of the fiber and the aryl sulfone fiber is 15 mm, the graphite particles are divided into large graphite particles and small graphite particles, the particle diameters of the large graphite particles and the small graphite particles are 80 μm and 30 μm respectively, the mass ratio between the large graphite particles and the small graphite particles is 1:4, the graphite particles are modified by aluminum sol, and the modification process is to immerse the graphite particles in nano-aluminum sol for 2 hours, the solid particle size diameter in the nano-aluminum sol is 20 nm, the concentration of the nano-aluminum sol is 15%, and it is heated to 285°C for 2 hours to obtain a high temperature resistant nylon material.
[0061] S5: Casting the high temperature resistant nylon material into a mold preheated to 180° C. and always maintaining the mold temperature for 30 minutes and then cooling naturally. Centrifugal treatment is performed during the cooling process to obtain the high temperature resistant monomer cast nylon material.
[0062] Embodiment 5
[0063] This embodiment provides a high temperature resistant monomer cast nylon material, and the preparation process is as follows: S1: heating the laurolactam monomer with a monomer diameter of 12 μm to a molten state in a closed environment, the heating condition is a constant temperature oil bath of 270° C., the heating time after the molten state is 60 minutes, and vacuum treatment is performed in the molten state to obtain molten laurolactam.
[0064] S2: vinyl alcohol, acetyl caprolactam and distearoyloxyisopropyl aluminate are added to molten laurolactam in sequence, the mass ratio of vinyl alcohol, acetyl caprolactam and distearoyloxyisopropyl aluminate is 1:2:3, the mass ratio of the total mass of vinyl alcohol, acetyl caprolactam and distearoyloxyisopropyl aluminate to the molten laurolactam is 40:1, and after stirring, heating is continued at 280°C for 20 minutes; polymerized laurolactam is obtained.
[0065] S3: Add N-dimethyl-N-(acryloyloxyethyl)-N-(2-hydroxyethyl) ammonium chloride and dibutyltin dilaurate to polymerized laurolactam, the mass ratio of polymerized laurolactam, N-dimethyl-N-(acryloyloxyethyl)-N-(2-hydroxyethyl) ammonium chloride and dibutyltin dilaurate is 100:4:1, and stir at 250°C for 1h to obtain a modified nylon material.
[0066] S4: basalt fiber, sulfone fiber, graphite particles and distearoyloxyisopropylaluminate are added to the modified nylon material in sequence, the mass ratio of the added distearoyloxyisopropylaluminate to the distearoyloxyisopropylaluminate in the modified nylon material is 2:3, the mass ratio of basalt fiber, sulfone fiber and graphite particles is 6:3; 2, the mass ratio of the total mass of basalt fiber, sulfone fiber and graphite particles to the modified nylon material is 1:4, the fineness of basalt fiber and sulfone fiber is 8D and 6D respectively, the basalt fiber is 1:4, the fineness of basalt fiber and sulfone fiber is 8D and 6D respectively, the mass ratio of basalt fiber to basalt fiber is 1:4, the mass ratio of basalt fiber to sulfone ... The length of the fiber and the aryl sulfone fiber is 15 mm, the graphite particles are divided into large graphite particles and small graphite particles, the particle diameters of the large graphite particles and the small graphite particles are 80 μm and 30 μm respectively, the mass ratio between the large graphite particles and the small graphite particles is 1:4, the graphite particles are modified by aluminum sol, and the modification process is to immerse the graphite particles in nano-aluminum sol for 2 hours, the solid particle size diameter in the nano-aluminum sol is 20 nm, the concentration of the nano-aluminum sol is 15%, and it is heated to 285°C for 2 hours to obtain a high temperature resistant nylon material.
[0067] S5: Casting the high temperature resistant nylon material into a mold preheated to 180° C. and always maintaining the mold temperature for 30 minutes and then cooling naturally. Centrifugal treatment is performed during the cooling process to obtain the high temperature resistant monomer cast nylon material.
[0068] Embodiment 6
[0069] This embodiment provides a high temperature resistant monomer cast nylon material, and the preparation process is as follows: S1: heating the laurolactam monomer with a monomer diameter of 12 μm to a molten state in a closed environment, the heating condition is a constant temperature oil bath of 270° C., the heating time after the molten state is 60 minutes, and vacuum treatment is performed in the molten state to obtain molten laurolactam.
[0070] S2: vinyl alcohol, acetyl caprolactam and distearoyloxyisopropyl aluminate are added to molten laurolactam in sequence, the mass ratio of vinyl alcohol, acetyl caprolactam and distearoyloxyisopropyl aluminate is 1:2:3, the mass ratio of the total mass of vinyl alcohol, acetyl caprolactam and distearoyloxyisopropyl aluminate to the molten laurolactam is 40:1, and after stirring, heating is continued at 280°C for 20 minutes; polymerized laurolactam is obtained.
[0071] S3: Add N-dimethyl-N-(acryloyloxyethyl)-N-(2-hydroxyethyl) ammonium chloride and dibutyltin dilaurate to polymerized laurolactam, the mass ratio of polymerized laurolactam, N-dimethyl-N-(acryloyloxyethyl)-N-(2-hydroxyethyl) ammonium chloride and dibutyltin dilaurate is 100:4:1, and stir at 250°C for 1h to obtain a modified nylon material.
[0072] S4: basalt fiber, sulfone fiber, graphite particles and distearoyloxyisopropylaluminate are added to the modified nylon material in sequence, the mass ratio of the added distearoyloxyisopropylaluminate to the distearoyloxyisopropylaluminate in the modified nylon material is 2:3, the mass ratio of basalt fiber, sulfone fiber and graphite particles is 6:3; 2, the mass ratio of the total mass of basalt fiber, sulfone fiber and graphite particles to the modified nylon material is 1:8, the fineness of basalt fiber and sulfone fiber is 8D and 6D respectively, the basalt fiber is 1:8, the fineness of basalt fiber and sulfone fiber is 8D and 6D respectively, the mass ratio of basalt fiber to graphite particles is 1:8, the mass ratio of basalt fiber to sulfone fiber ... The length of the fiber and the aryl sulfone fiber is 15 mm, the graphite particles are divided into large graphite particles and small graphite particles, the particle diameters of the large graphite particles and the small graphite particles are 80 μm and 30 μm respectively, the mass ratio between the large graphite particles and the small graphite particles is 1:3, the graphite particles are modified by aluminum sol, and the modification process is to immerse the graphite particles in nano-aluminum sol for 2 hours, the solid particle size diameter in the nano-aluminum sol is 20 nm, the concentration of the nano-aluminum sol is 15%, and it is heated to 285°C for 2 hours to obtain a high temperature resistant nylon material.
[0073] S5: Casting the high temperature resistant nylon material into a mold preheated to 180° C. and always maintaining the mold temperature for 30 minutes and then cooling naturally. Centrifugal treatment is performed during the cooling process to obtain the high temperature resistant monomer cast nylon material.
[0074] Embodiment 7
[0075] This embodiment provides a high temperature resistant monomer cast nylon material, and the preparation process is as follows: S1: heating the laurolactam monomer with a monomer diameter of 12 μm to a molten state in a closed environment, the heating condition is a constant temperature oil bath of 270° C., the heating time after the molten state is 60 minutes, and vacuum treatment is performed in the molten state to obtain molten laurolactam.
[0076] S2: vinyl alcohol, acetyl caprolactam and distearoyloxyisopropyl aluminate are added to molten laurolactam in sequence, the mass ratio of vinyl alcohol, acetyl caprolactam and distearoyloxyisopropyl aluminate is 1:2:3, the mass ratio of the total mass of vinyl alcohol, acetyl caprolactam and distearoyloxyisopropyl aluminate to the molten laurolactam is 40:1, and after stirring, heating is continued at 280°C for 20 minutes; polymerized laurolactam is obtained.
[0077] S3: Add N-dimethyl-N-(acryloyloxyethyl)-N-(2-hydroxyethyl) ammonium chloride and dibutyltin dilaurate to polymerized laurolactam, the mass ratio of polymerized laurolactam, N-dimethyl-N-(acryloyloxyethyl)-N-(2-hydroxyethyl) ammonium chloride and dibutyltin dilaurate is 100:4:1, and stir at 250°C for 1h to obtain a modified nylon material.
[0078] S4: basalt fiber, sulfone fiber, graphite particles and distearoyloxyisopropylaluminate are added to the modified nylon material in sequence, the mass ratio of the added distearoyloxyisopropylaluminate to the distearoyloxyisopropylaluminate in the modified nylon material is 2:3, the mass ratio of basalt fiber, sulfone fiber and graphite particles is 6:3; 2, the mass ratio of the total mass of basalt fiber, sulfone fiber and graphite particles to the modified nylon material is 1:8, the fineness of basalt fiber and sulfone fiber is 8D and 6D respectively, the basalt fiber is 1:8, the fineness of basalt fiber and sulfone fiber is 8D and 6D respectively, the mass ratio of basalt fiber to graphite particles is 1:8, the mass ratio of basalt fiber to sulfone fiber ... The length of the fiber and the aryl sulfone fiber is 15 mm, the graphite particles are divided into large graphite particles and small graphite particles, the particle diameters of the large graphite particles and the small graphite particles are 80 μm and 30 μm respectively, the mass ratio between the large graphite particles and the small graphite particles is 1:5, the graphite particles are modified by aluminum sol, and the modification process is to immerse the graphite particles in nano-aluminum sol for 2 hours, the solid particle size diameter in the nano-aluminum sol is 20 nm, the concentration of the nano-aluminum sol is 15%, and it is heated to 285°C for 2 hours to obtain a high temperature resistant nylon material.
[0079] S5: Casting the high temperature resistant nylon material into a mold preheated to 180° C. and always maintaining the mold temperature for 30 minutes and then cooling naturally. Centrifugal treatment is performed during the cooling process to obtain the high temperature resistant monomer cast nylon material.
[0080] Embodiment 8
[0081] This embodiment provides a high temperature resistant monomer cast nylon material, and the preparation process is as follows: S1: heating the laurolactam monomer with a monomer diameter of 12 μm to a molten state in a closed environment, the heating condition is a constant temperature oil bath of 270° C., the heating time after the molten state is 60 minutes, and vacuum treatment is performed in the molten state to obtain molten laurolactam.
[0082] S2: vinyl alcohol, acetyl caprolactam and distearoyloxyisopropyl aluminate are added to molten laurolactam in sequence, the mass ratio of vinyl alcohol, acetyl caprolactam and distearoyloxyisopropyl aluminate is 1:2:3, the mass ratio of the total mass of vinyl alcohol, acetyl caprolactam and distearoyloxyisopropyl aluminate to the molten laurolactam is 40:1, and after stirring, heating is continued at 280°C for 20 minutes; polymerized laurolactam is obtained.
[0083] S3: Add N-dimethyl-N-(acryloyloxyethyl)-N-(2-hydroxyethyl) ammonium chloride and dibutyltin dilaurate to polymerized laurolactam, the mass ratio of polymerized laurolactam, N-dimethyl-N-(acryloyloxyethyl)-N-(2-hydroxyethyl) ammonium chloride and dibutyltin dilaurate is 100:4:1, and stir at 250°C for 1h to obtain a modified nylon material.
[0084] S4: basalt fiber, sulfone fiber, graphite particles and distearoyloxyisopropylaluminate are added to the modified nylon material in sequence, the mass ratio of the added distearoyloxyisopropylaluminate to the distearoyloxyisopropylaluminate in the modified nylon material is 2:3, the mass ratio of basalt fiber, sulfone fiber and graphite particles is 6:3; 2, the mass ratio of the total mass of basalt fiber, sulfone fiber and graphite particles to the modified nylon material is 1:8, the fineness of basalt fiber and sulfone fiber is 8D and 6D respectively, the basalt fiber is 1:8, the fineness of basalt fiber and sulfone fiber is 8D and 6D respectively, the mass ratio of basalt fiber to graphite particles is 1:8, the mass ratio of basalt fiber to sulfone fiber ... The length of the fiber and the aryl sulfone fiber is 15 mm, the graphite particles are divided into large graphite particles and small graphite particles, the particle diameters of the large graphite particles and the small graphite particles are 80 μm and 30 μm respectively, the mass ratio between the large graphite particles and the small graphite particles is 1:6, the graphite particles are modified by aluminum sol, and the modification process is to immerse the graphite particles in nano-aluminum sol for 2 hours, the solid particle size diameter in the nano-aluminum sol is 20 nm, the concentration of the nano-aluminum sol is 15%, and it is heated to 285°C for 2 hours to obtain a high temperature resistant nylon material.
[0085] S5: Casting the high temperature resistant nylon material into a mold preheated to 180° C. and always maintaining the mold temperature for 30 minutes and then cooling naturally. Centrifugal treatment is performed during the cooling process to obtain the high temperature resistant monomer cast nylon material.
[0086] Embodiment 9
[0087] This embodiment provides a high temperature resistant monomer cast nylon material, and the preparation process is as follows: S1: heating the laurolactam monomer with a monomer diameter of 12 μm to a molten state in a closed environment, the heating condition is a constant temperature oil bath of 270° C., the heating time after the molten state is 60 minutes, and vacuum treatment is performed in the molten state to obtain molten laurolactam.
[0088] S2: vinyl alcohol, acetyl caprolactam and distearoyloxyisopropyl aluminate are added to molten laurolactam in sequence, the mass ratio of vinyl alcohol, acetyl caprolactam and distearoyloxyisopropyl aluminate is 1:2:3, the mass ratio of the total mass of vinyl alcohol, acetyl caprolactam and distearoyloxyisopropyl aluminate to the molten laurolactam is 40:1, and after stirring, heating is continued at 280°C for 20 minutes; polymerized laurolactam is obtained.
[0089] S3: Add N-dimethyl-N-(acryloyloxyethyl)-N-(2-hydroxyethyl) ammonium chloride and dibutyltin dilaurate to polymerized laurolactam, the mass ratio of polymerized laurolactam, N-dimethyl-N-(acryloyloxyethyl)-N-(2-hydroxyethyl) ammonium chloride and dibutyltin dilaurate is 100:4:1, and stir at 250°C for 1h to obtain a modified nylon material.
[0090] S4: basalt fiber, sulfone fiber, graphite particles and distearoyloxyisopropylaluminate are added to the modified nylon material in sequence, the mass ratio of the added distearoyloxyisopropylaluminate to the distearoyloxyisopropylaluminate in the modified nylon material is 2:3, the mass ratio of basalt fiber, sulfone fiber and graphite particles is 6:3; 2, the mass ratio of the total mass of basalt fiber, sulfone fiber and graphite particles to the modified nylon material is 1:8, the fineness of basalt fiber and sulfone fiber is 8D and 6D respectively, the basalt fiber is 1:8, the fineness of basalt fiber and sulfone fiber is 8D and 6D respectively, the mass ratio of basalt fiber to graphite particles is 1:8, the mass ratio of basalt fiber to sulfone fiber ... The length of the fiber and the aryl sulfone fiber is 15 mm, the graphite particles are divided into large graphite particles and small graphite particles, the particle diameters of the large graphite particles and the small graphite particles are 80 μm and 30 μm respectively, the mass ratio between the large graphite particles and the small graphite particles is 1:7, the graphite particles are modified by aluminum sol, and the modification process is to immerse the graphite particles in nano aluminum sol for 2 hours, the solid particle size diameter in the nano aluminum sol is 20 nm, the concentration of the nano aluminum sol is 15%, and it is heated to 285°C for 2 hours to obtain a high temperature resistant nylon material.
[0091] S5: Casting the high temperature resistant nylon material into a mold preheated to 180° C. and always maintaining the mold temperature for 30 minutes and then cooling naturally. Centrifugal treatment is performed during the cooling process to obtain the high temperature resistant monomer cast nylon material.
[0092] Comparative Example 1 This comparative example provides a monomer cast nylon material, and the preparation process is as follows: S1: heating the laurolactam monomer with a monomer diameter of 12 μm to a molten state in a closed environment, the heating condition is a constant temperature oil bath of 270° C., the heating time after the molten state is 60 minutes, and vacuum treatment is performed in the molten state to obtain molten laurolactam.
[0093] S2: vinyl alcohol, acetyl caprolactam and distearoyloxyisopropyl aluminate are added to molten laurolactam in sequence, the mass ratio of vinyl alcohol, acetyl caprolactam and distearoyloxyisopropyl aluminate is 1:2:3, the mass ratio of the total mass of vinyl alcohol, acetyl caprolactam and distearoyloxyisopropyl aluminate to the molten laurolactam is 40:1, and after stirring, heating is continued at 280°C for 20 minutes; polymerized laurolactam is obtained.
[0094] S3: Casting the polymerized laurolactam into a mold preheated to 180° C. and maintaining the mold temperature for 30 minutes and then cooling naturally. During the cooling process, centrifugal treatment is performed to obtain a monomer cast nylon material.
[0095] Samples of the materials in Examples 1 to 9 and Comparative Example 1 were taken, and the friction coefficient of the materials was tested according to GB / T3960-2016, and the tensile strength of the samples was tested according to GB / T1040.5-2008. The friction coefficient and tensile strength were measured after heating at 150° C. for 2 h, respectively. The measurement data are shown in Table 1.
[0096] Table 1 Self-lubricating property and tensile strength experimental data of Examples 1 to 9 and Comparative Example 1
[0097] As shown in Table 1, the friction coefficients in Examples 1 to 9 are all lower than those in Comparative Example 1, and the tensile strengths in Examples 1 to 9 are all greater than those in Comparative Example 1. The high temperature resistant monomer cast nylon material in the present application can increase the self-lubricity and tensile strength at high temperatures.
[0098] In embodiments one to five, as the mass ratio between the total mass of basalt fiber, sulfonamide fiber and graphite particles and the modified nylon material gradually decreases, the friction coefficient first decreases and then increases, and the tensile strength first increases and then decreases. This is because the addition of fiber and graphite particles improves the microstructure of the material, reduces the porosity and inhomogeneity inside the material, and graphite particles provide self-lubrication. Excessive reinforcement materials and fillers may cause them to be unevenly distributed in the matrix, causing agglomeration or forming larger aggregates. This inhomogeneity increases the roughness of the material surface, thereby increasing the friction coefficient; the addition of reinforcement materials and fillers will increase the tensile strength of the composite material. The rigidity of basalt fiber, sulfonamide fiber and graphite particles is higher than that of the nylon matrix, so they can improve the material's compression and deformation resistance, but excessive reinforcement materials and fillers cause the interface bonding between the matrix and the reinforcement to deteriorate, resulting in a decrease in structural strength and a decrease in rigidity. The preferred embodiment is embodiment three.
[0099] In embodiment three and embodiment six to nine, as the mass ratio between large graphite particles and small graphite particles increases gradually, the friction coefficient first decreases and then increases, and the tensile strength first increases and then decreases. Increasing the ratio of small graphite particles can improve the self-lubricating property of the material. Small graphite particles may be easier to fill in the microscopic pores on the surface of the material to form a smoother surface, thereby reducing the friction coefficient. But when the ratio of small graphite particles is too high, small graphite particles will be more easily worn during the friction process, producing fine wear particles, and these particles will increase the friction of the contact surface. When the ratio of small graphite particles increases, due to the small particle diameter, it is easy to be evenly distributed, improves the finishing mechanical properties, but the interface bonding between small graphite particles and nylon matrix is not as strong as large particles, and too many small particles can cause the overall interface bonding strength to decrease, causing the tensile strength to decrease, and the best embodiment is embodiment seven.
[0100] The above is based on the ideal embodiment of the present invention. Through the above description, relevant personnel can make various changes and modifications without departing from the technical concept of the present invention. The technical scope of the present invention is not limited to the content in the specification, and the technical scope must be determined according to the scope of the claims.
Claims
1. A high temperature resistant monomer cast nylon material, characterized in that: It consists of component A, component B and component C, wherein: The A component is laurolactam; The B component includes: basalt fiber, high temperature resistant fiber and graphite particles, and the mass ratio of the basalt fiber, the high temperature resistant fiber and the graphite particles is: 100-120:50-60:30-40; The C component includes: a catalyst, a co-catalyst and a surface modifier, and the mass ratio of the catalyst, the co-catalyst and the surface modifier is: 1-10:10-14:10-25; The mass ratio of the A component, the B component and the C component is 84:100:10-14:3-5.
2. The high temperature resistant monomer cast nylon material according to claim 1, characterized in that: The basalt fiber is prepared based on basalt ore. The raw materials for preparing the basalt fiber include basalt ore, quartz sand, quicklime, a wetting agent and a coupling agent, wherein the mass proportion of the basalt ore is greater than 65%.
3. The high temperature resistant monomer cast nylon material according to claim 1, characterized in that: The high temperature resistant fiber is aromatic sulfone fiber, and the fineness of the high temperature resistant fiber is 5D-7D.
4. The high temperature resistant monomer cast nylon material according to claim 1, characterized in that: The graphite particles include large graphite particles and small graphite particles, the particle diameters of the large graphite particles and the small graphite particles are 60-100 μm and 20-40 μm, respectively, and the mass ratio between the large graphite particles and the small graphite particles is 1:4-6.
5. The high temperature resistant monomer cast nylon material according to claim 1, characterized in that: The fineness of the basalt fiber is 6D-10D, and the length of the basalt fiber is consistent with the length of the high temperature resistant fiber.
6. The high temperature resistant monomer cast nylon material according to claim 1, characterized in that: The catalyst, the co-catalyst and the surface modifier are respectively vinyl alcohol, acetyl caprolactam and distearoyloxyisopropylaluminate.
7. A method for preparing a high temperature resistant monomer cast nylon material, according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1: heating the laurolactam monomer to a molten state in a closed environment, the heating condition is a constant temperature oil bath of 270-300° C., the heating time after the molten state is 30-60 minutes, and vacuuming is performed in the molten state to obtain molten laurolactam; S2: adding a catalyst to the molten laurolactam, and continuing to heat at 270-280° C. for 20-30 min after stirring to obtain polymerized laurolactam; S3: adding quaternary ammonium salt powder to the polymerized laurolactam, wherein the mass ratio of the polymerized laurolactam to the quaternary ammonium salt powder is 20-30:1, and stirring at a temperature of 240-260° C. for 1-2 hours to obtain a modified nylon material; S4: adding basalt fiber, high temperature resistant fiber and graphite particles to the modified nylon material in sequence, and heating to 285-300° C. for 2-4 hours to obtain a high temperature resistant nylon material; S5: Casting the high temperature resistant nylon material into a mold preheated to 160-180° C., and always maintaining the mold temperature for 20-30 minutes and then cooling naturally, performing centrifugal treatment during the cooling process, to obtain a high temperature resistant monomer cast nylon material.
8. The method for preparing a high temperature resistant monomer cast nylon material according to claim 7, characterized in that: The graphite particles are modified by aluminum sol, and the modification process is to immerse the graphite particles in nano aluminum sol for 1.5-2 hours, the diameter of the solid particles in the nano aluminum sol is 10-30nm, and the concentration of the nano aluminum sol is 15-25%.
9. The method for preparing a high temperature resistant monomer cast nylon material according to claim 7, characterized in that: The diameter of the laurolactam monomer is 10-14 μm, and the length of the basalt fiber is 15-18 mm.
10. An application of a high temperature resistant monomer cast nylon material, based on the high temperature resistant monomer cast nylon material according to any one of claims 1 to 6, characterized in that: The high temperature resistant monomer cast nylon material is applied to bearings and bearing sleeves.
Citation Information
Patent Citations
Carbon-based nano cast nylon composite material and in-situ polymerization preparation method thereof
CN101928457A
Treatment process for engineering plastic for busways
CN104927352A
Molten material splashing-preventing fabric and protective clothing
CN113882059A
Aviation fuel tank and preparation method thereof
CN113969056A
Ethylene-propylene-diene monomer rubber with low density, ablation resistance and good mechanical property and preparation method of ethylene-propylene-diene monomer rubber
CN118638365A